mGluR1 enhances efferent inhibition of inner hair cells in the developing rat cochlea - Ye, Zhanlei (2017)
Key points: Spontaneous activity of the sensory inner hair cells shapes maturation of the developing ascending (afferent) auditory system before hearing begins. Just before the onset of hearing, descending (efferent) input from cholinergic neurons originating in the brainstem inhibit inner hair cell spontaneous activity and may further refine maturation. We show that agonist activation of the group I metabotropic glutamate receptor mGluR1 increases the strength of this efferent inhibition by enhancing the presynaptic release of acetylcholine. We further show that the endogenous release of glutamate from the inner hair cells may increase the strength of efferent inhibition via the activation of group I metabotropic glutamate receptors. Thus, before the onset of hearing, metabotropic glutamate signalling establishes a local negative feedback loop that is positioned to regulate inner hair cell excitability and refine maturation of the auditory system. Abstract: Just before the onset of hearing, the inner hair cells (IHCs) receive inhibitory efferent input from cholinergic medial olivocochlear (MOC) neurons originating in the brainstem. This input may serve a role in the maturation of the ascending (afferent) auditory system by inhibiting spontaneous activity of the IHCs. To investigate the molecular mechanisms regulating these IHC efferent synapses, we combined electrical stimulation of the efferent fibres with patch clamp recordings from the IHCs to measure efferent synaptic strength. By examining evoked responses, we show that activation of metabotropic glutamate receptors (mGluRs) by general and group I-specific mGluR agonists enhances IHC efferent inhibition. This enhancement is blocked by application of a group I mGluR1-specific antagonist, indicating that enhancement of IHC efferent inhibition is mediated by group I mGluRs and specifically by mGluR1s. By comparing spontaneous and evoked responses, we show that group I mGluR agonists act presynaptically to increase neurotransmitter release without affecting postsynaptic responsiveness. Moreover, endogenous glutamate released from the IHCs also enhances IHC efferent inhibition via the activation of group I mGluRs. Finally, immunofluorescence analysis indicates that the efferent terminals are sufficiently close to IHC glutamate release sites to allow activation of mGluRs on the efferent terminals by glutamate spillover. Together, these results suggest that glutamate released from the IHCs activates group I mGluRs (mGluR1s), probably present on the efferent terminals, which, in turn, enhances release of acetylcholine and inhibition of the IHCs. Thus, mGluRs establish a local negative feedback loop positioned to regulate IHC activity and maturation of the ascending auditory system in the developing cochlea.